Transition‐Metal‐Free Amination of Aryl boronic Acids and Their Derivatives. Issue 22 (19th April 2013) - Coeffard, Vincent; Moreau, Xavier; Thomassigny, Christine; Greck, Christine
<x xml:space="preserve">Abstract</x> Free rein: Advances in transition‐metal‐free direct amination of aryl boronic acids and their derivatives have been recently described (see scheme). These reactions are based on the use of hydroxylamine or azide derivatives and offer great potential for further applications.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>